2016
DOI: 10.1186/s12978-016-0156-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating paternal preconception risk factors for adverse pregnancy outcomes in a population of internet users

Abstract: BackgroundPaternal preconception risk factors such as smoking, exposure to environmental substances, medication use, overweight and advanced age correlate with the occurrence of malformations and birth defects in the offspring. Nonetheless, the prevalence of risk factors for adverse pregnancy outcomes in the male population has been scarcely investigated and no report on preconception interventions targeting prospective fathers is available. We conducted a web-based survey to measure the prevalence of paternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…via biological effects in sperm) and indirect (e.g. via influence on the mother) paternal effects in DOHaD ( Agricola et al, 2016 ; Braun et al, 2017 ; Day et al, 2016 ; Romanus et al, 2016 ; Soubry, 2017 ). This goes hand-in-hand with developing and implementing strategies to collect better-quality, more complete data on partners.…”
Section: Strategies To Maintain a Critical Perspectivementioning
confidence: 99%
“…via biological effects in sperm) and indirect (e.g. via influence on the mother) paternal effects in DOHaD ( Agricola et al, 2016 ; Braun et al, 2017 ; Day et al, 2016 ; Romanus et al, 2016 ; Soubry, 2017 ). This goes hand-in-hand with developing and implementing strategies to collect better-quality, more complete data on partners.…”
Section: Strategies To Maintain a Critical Perspectivementioning
confidence: 99%
“…There was a notable absence of the concept of the "preconception population" in the literature, however the term "preconception" was broadly used in the context of women's health before or around pregnancy or conception. For example, some documents focused on preconception care and related needs [41,42], while others were focused on preconception health as a concept [11,22]. Studies tended to define preconception as a time period rather than a population, for example referring to women before conception [33] or before a pregnancy [24,28], or using "time to pregnancy" as a measure of the preconception period [33].…”
Section: Recruitment Methodsmentioning
confidence: 99%
“…Regarding inclusion criteria of participants, most studies specified recruitment of women only (n = 13), with one solely recruiting men [22]. Age criteria varied, albeit most (n = 12) studies recruited participants aged 18 to 45 years.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…While the data on pregnancy are limited, we know little about paternal drug exposure. Paternal obesity, age and smoking are associated with a low increase of risk; but it is remarkable that after decades of chemotherapy research, no single drug has been identified that causes malformations in offspring after paternal exposure, although they may cause infertility.…”
mentioning
confidence: 99%